Can the central environmental protection inspection improve urban energy utilization efficiency? - Tang, Baoshi; Zhong, Yu; Zuo, Zhizhao; Xie, Xusheng (Frontiers in Environmental Science, 2025)
Using a panel dataset of Chinese cities from 2007 to 2020, this paper evaluates the impact of the Central Environmental Protection Inspection (CEPI) on urban Energy Utilization Efficiency by employing a staggered difference-in-differences design. The analysis yields four key findings. First, CEPI significantly improves cities’ Energy Utilization Efficiency, and this result remains robust across a battery of empirical checks, including sensitivity analyses for deviations from the parallel trends assumption, estimation using imperfect instrumental variables, and heterogeneous treatment effects. Second, mechanism analysis suggests that CEPI enhances urban innovation capacity, discourages the entry of pollution-intensive firms, and mitigates capital misallocation. Third, heterogeneity analysis reveals that the positive effects of CEPI on Energy Utilization Efficiency are more pronounced in resource-based cities, cities with weaker environmental enforcement, and those with higher levels of green financial development. Fourth, extending the analysis using a Double Machine Learning framework, we further find that CEPI contributes to improvements in cities’ inclusive green growth. Taken together, these findings offer new insights for developing economies—such as China—seeking to improve Energy Utilization Efficiency through institutionalized environmental regulatory mechanisms.